CURRENT STATE AND PROBLEMS OF ENTREPRENEURSHIP DEVELOPMENT IN UKRAINE - SACHYNSKA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines different approaches to the definition of entrepreneurship that have evolved historically. A detailed analysis of the number of large, medium, small, and micro businesses in recent years is carried out. It is noted that in Ukraine today, there are many problems that impede the development of entrepreneurship, the solution of which will increase the efficiency of entrepreneurial activity, expand the entrepreneurial sector, and reduce the shadow sector. The main role in these transformations should be played by the state. The main problems of entrepreneurship development are highlighted: a full-scale war; reduction of investments, lack of incentives for investment, constant shelling, insecurity in the country, problems with access to credit, lack of collateral, the highest interest rates of commercial banks; inaccessibility of credit resources for starting and running a business or its restoration; high level of taxation (payroll taxes; inability to show the real financial condition (losses of the enterprise); inability to return to the impossibility of VAT refund; a large number of different direct and indirect taxes and fees; burdensome reporting system; constant changes in the legislative framework; uncertainty of entrepreneurs in the stability of business conditions (contradictions between legislative acts; insecurity against raider attacks related to corruption of the judicial system and inefficiency of the executive service; lack of a clearly defined state policy in the field of business support; increase in administrative barriers (registration, licensing, certification, etc.); and excessive interference of public authorities in the activities of business entities; high levels of corruption, unstable conditions and raiding; lack of qualified personnel, lack of practical skills of entrepreneurial employees in doing business, imperfect system of training, retraining and advanced training of personnel for entrepreneurial activities.